Student Peer Assessment on the Amphibious Dissection Practices - Ratnasari, Dwi; Hendriyani, Mila Ermila; Nulhakim, Lukman (Jurnal Penelitian dan Pembelajaran IPA, 2017)
The aims of this research to determine the implementation and the responses of students about peer assessment in assessing the performance of amphibious dissection practices. This research method was descriptive research with the subject of X1 and X3 grade students in SMAN 1 Ciomas. The result showed that both of the classes have the ability to peer assessment sufficient. Performance capability according to peer assessment and observer in superior class and regular class entered in very good category. Student’s response on peer assessment was good. Students were enthusiastic in doing peer assessment because it directly involved in the assessment. Keywords: Implementation of Practice, Peer Assessment, Performance